A Descriptive Study On The Vocabulary Mastery of Tenth Year Students Of SMK Al Maksum Stabat - Lestari, Neneng; Yunita Sari Adelina; Edi Suprayetno (Jurnal Mutiara Pendidikan Indonesia, 2022)
This study deals with the discussion of vocabulary. The problem in this research is "how far is the ability of tenth graders of Al Maksum Stabat Vocational High School in understanding and remembering vocabulary. The purpose of this research is to get an overview of students' ability to master vocabulary and to find out what difficulties students face in mastering vocabulary. The population of this study was tenth grade students of SMK Al Maksum Stabat which consisted of 120 students from three parallel classes. For the sample, only 40% of the population was taken, namely 50 students. This research instrument uses an objective test. This research method is field research. After the data was analyzed, it was found that the average or mean value of the students was 78.51. It can be concluded that the ability of the tenth grade students is "good", and it is suggested that the English teacher give a lot of practice, especially with regard to vocabulary.